2018
DOI: 10.1016/j.cbpb.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of wastewater treatment plant effluent on energetics and stress response of rainbow darter (Etheostoma caeruleum) in the Grand River watershed

Abstract: The objective of this study was to assess the effects of municipal wastewater treatment plant effluent on the energetics and stress response of rainbow darter (Etheostoma caeruleum). Male and female rainbow darter were collected upstream and downstream of the Waterloo WWTP in the Grand River watershed, ON, Canada. To assess the effects of wastewater treatment plant effluent on whole-body and tissue specific metabolic capacity, closed-chamber respirometry and muscle-enzyme activity analyses were performed. Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 97 publications
5
24
1
Order By: Relevance
“…Our results also indicate that VFX and temperature may be working cumulatively, as RMR was highest in the multi-stressed group. This is in line with other studies that have demonstrated the effects of various contaminants on metabolic rate, such as polychlorinated biphenyls, metals (McGeer et al, 2000), metals (Rajotte and Couture, 2002), and wastewater effluent (Du et al, 2018, 2019; Mehdi et al, 2018). At the tissue level, we demonstrated elevation in muscle glucose levels in the multi-stressed group compared to the Control , and increased PK activity in both Temp and VFX & Temp relative to Control and VFX .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results also indicate that VFX and temperature may be working cumulatively, as RMR was highest in the multi-stressed group. This is in line with other studies that have demonstrated the effects of various contaminants on metabolic rate, such as polychlorinated biphenyls, metals (McGeer et al, 2000), metals (Rajotte and Couture, 2002), and wastewater effluent (Du et al, 2018, 2019; Mehdi et al, 2018). At the tissue level, we demonstrated elevation in muscle glucose levels in the multi-stressed group compared to the Control , and increased PK activity in both Temp and VFX & Temp relative to Control and VFX .…”
Section: Discussionsupporting
confidence: 92%
“…1.11.1.6). Enzyme assays were performed following the protocols described in Mehdi et al (2018). For reference, enzyme activities were also measured at assay temperatures matching both exposure temperatures (27–32°C), data shown in Supplementary Materials (Supplementary Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study done in natural water bodies receiving treated wastewater and containing estrogens, revealed seasonal changes in the HSI, but these did not correlate to plasma vitellogenin concentrations [73], supporting the assumption that elevated vitellogenesis in the liver caused by exposure to estrogenic factors is not the only cause for changes in HSI. Elevated HSI in fish may indicate stress response to TWW exposure and the different contaminants it contains (estrogenic and non-estrogenic), resulting in elevated hepatic lipid content and altered activity, such as gluconeogenesis and glycolysis [74,75].…”
Section: Resultsmentioning
confidence: 99%